Margin Sampling and Survival Outcomes in Oral Cavity and p16‐Positive Oropharyngeal Squamous Cell Carcinoma. Issue 3 (21st September 2022) - MacKay, Colin; Turner, Brooke; Bullock, Martin; Taylor, S. Mark; Trites, Jonathan; Corsten, Martin; Geldenhuys, Laurette; Rigby, Matthew H.
Abstract : Objective: To compare the association of margin sampling technique on survival outcomes in surgically treated cT1‐2 oral cavity and oropharyngeal squamous cell carcinoma. Study Design: A prospective longitudinal cohort study. Setting: Tertiary care academic teaching hospital in Halifax, Nova Scotia. Methods: All cases of surgically treated cT1‐2 oral cavity and oropharyngeal cancer undergoing specimen‐oriented margin analysis between January 1, 2017, and December 31, 2018 were analyzed. The specimen‐oriented cohort was compared with a cohort of patients from January 1, 2009, to December 31, 2014, where a defect‐oriented margin sampling protocol was used. Kaplan‐Meier survival curves were used to estimate 2‐year overall survival, disease‐specific survival, local control, and recurrence‐free survival rates in oral cavity and p16‐positive oropharyngeal squamous cell carcinoma. Cox proportional hazards models were used to assess the effect of margin sampling method on disease‐specific survival and local control. Results: There was no significant association between margin sampling technique and 2‐year survival outcomes for surgically treated cT1‐2 oral cavity and oropharyngeal squamous cell carcinoma. In the multivariate Cox proportional hazard model, the hazard ratio (HR) of specimen‐oriented sampling was not significantly different for disease‐specific survival (HR, 1.32; 95% CI, 0.3032‐5.727; P =. 713) or local control (HR, 0.4087; 95% CI, 0.0795‐2.099; P =. 284). Conclusion: Intraoperative margin sampling method was not associated with a significant change in 2‐year survival outcomes. Despite no effect on survival outcomes, implementation of a specimen‐oriented sampling method has potential for cost avoidance by decreasing the number of re‐resections for positive or close margins.